Eating Disorders and Eating Pattern During Covid-19 Pandemic: A Short Bulletin - Mahar, Benazir; Warsi, Jamshed; Shah, Tazeen (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To rule out possible effects of lockdown/self-isolation on eating behaviors and to determine development of eating disorders in the pandemic due to stress and anxiety, produced as a result of fear of chances to get infection or stress produced due to social isolation. Methodology: An online survey-based study was performed by the way of social media and other online networking modes from April-May 2020, the number of participants was n=313, online SCOFF questionnaire was given to participants aged between 18 to 38 years. Results: The SCOFF positive male were 66(47.5%) and female were114(65.5%) while Binge eating disorders positive males were 102 (73.4%) and female were 113(64.9%). Furthermore, The increased size of meal in isolation period was significantly (p-0.0009) associated with Binge eating disorders positive females. The change in food intake time during isolation was also significantly (P-0.03, P-0.01 and P-0.001 respectively) more in SCOFF +ve female, Binge eating disorders positive male/female. Addition of snacks /fried /frozen food was significantly (P-0.007, P-0.0003) more in Binge eating disorders positive male and female. Surprisingly, no any significant difference was observed when participants were asked about exercise or physical activity before or during novel corona virus pandemic, however, a big proportion of general population 63.5% people were involved in exercise and/physical activities which reduced to 34.5% during pandemic. Conclusion: Eating disorders and changed eating pattern along with less physical activity was observed during COVID-19 pandemic lockdown. KEY WORDS: COVID-19, Self- isolation, Eating habits, SCOFF.